EDUCANDY PLATFORM IN IMPROVING THE UNDERSTANDING OF ARABIC VOCABULARY FOR HIGH SCHOOL STUDENTS DURING THE PANDEMIC - Fitria, Aida; Roziqi, Muhammad Ainur (ALSINATUNA, 2022)
Students' understanding of Arabic vocabulary is one of the benchmarks for success in learning. The absence of the use of innovative and interactive learning media causes the Arabic learning process to be suboptimal. This study uses the educandy platform as a learning media to facilitate students in the learning process. This study aims to determine the effectiveness of the educandy platform in improving understanding of Arabic vocabulary. This study uses a quantitative approach to the type of experiment which aim of knowing whether there is an effect of giving or treating the research subject. The research instruments used for data collection were questionnaires and tests. The data presented in this study uses paired sample t-test analysis techniques and the N-Gain formula using pre-test and post-test scores. The results of this study describe a fairly high difference between the pre-test average value of 44.66 and post-test 85.17, there is a difference in the average learning outcomes between the pre-test and post-test with a sig value of 0.000 < 0,05, the effectiveness results with the N-Gain formula of 0.73 are included in the "high" category. Therefore, the educandy platform is quite effectively used to improve understanding of Arabic vocabulary.